2013
DOI: 10.1037/a0030149
|View full text |Cite
|
Sign up to set email alerts
|

Racial identification, racial composition, and substance use vulnerability among African American adolescents and young adults.

Abstract: Objective Two studies examined racial identity (RI) as a protective factor against substance-related cognitions and substance use among Black adolescents and young adults living in high versus low percentage Black social environments. Method Using structural equation modeling techniques, Study 1 examined longer term effects of RI on substance use cognitions and behaviors among 720 Black adolescents. Study 2 examined the impact of RI and percentage Black peer environment on alcohol use among 203 Black young a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 62 publications
2
39
0
Order By: Relevance
“…Moreover, the results indicated that both ethnic identity and school engagement have a negative relationship with marijuana use, which is consistent with the past literature (e.g., Bryant et al, 2000; Pugh & Bry, 2007; Stock et al, 2013). However, the relationship between these protective factors and marijuana use is more complex.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, the results indicated that both ethnic identity and school engagement have a negative relationship with marijuana use, which is consistent with the past literature (e.g., Bryant et al, 2000; Pugh & Bry, 2007; Stock et al, 2013). However, the relationship between these protective factors and marijuana use is more complex.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the authors also found that positive ethnic identity was linked with less substance use and antidrug values. Additionally, researchers have found that ethnic identity in African American adolescents is associated with less substance use (Stock et al, 2013). Ethnic identity is also protective against marijuana use specifically.…”
Section: Ethic Identity and Substance Usementioning
confidence: 99%
See 1 more Smart Citation
“…However, they also find that white youth do not receive the same benefit of attending minority schools, possibly because white youth are “not as sensitive to the norms that oppose” substance use (Johnson and Hoffmann 2000:404), thus leaving them at increased risk of use even in minority contexts. More recently, Stock and colleagues (2012) examine contextual effects on substance use for youths in Iowa and Georgia, as well as young adults in Washington, D.C. They find that, among black adolescents living in white neighborhoods, those with a lessened racial identity have the highest levels of alcohol use, but those with high racial identification did experience a buffering effect in that they are less likely to use substances despite greater access to them.…”
Section: Neighborhood Racial Composition and Adolescent Binge Drinkingmentioning
confidence: 99%
“…Additionally, health behaviors are influenced by shared social and environmental determinants such as social norms, media exposure, and public policy [7][8][9][10]. For example, movies and other entertainment media that portray unhealthy behaviors can promote these behaviors [9] whereas taxes can discourage them [11].…”
Section: Introductionmentioning
confidence: 99%